The influence of multi-morbidity and self-reported socio-economic standing on the prevalence of depression in an elderly Hong Kong population - Leung Jason; Woo Jean; Mercer Stewart W; Wong Samuel YS (BMC, 2008)
Abstract Background There has been an increasing prevalence of both depression and chronic medical conditions globally but the relationship between depression and multi-morbidity is not well understood. The aim of the present study was to investigate the relationship between depression, multi-morbidity (number of chronic medical conditions, and measures of socioeconomic standing (SES) in an elderly Hong Kong population. Methods Cross sectional study. Information on clinically relevant depressive symptoms, measured by the Geriatric Depression Scale (GDS), and demographic and chronic medical conditions were collected using standardized questionnaires. Information collected on SES included educational status (ES), maximum ever income (MEI), and self-perceived social standing in local community (SES-COM) and in Hong Kong generally (SES-HK). Analysis was conducted using multiple logistic regression Results Depression rates were similar in men and women (GDS caseness 8.1% vs 8.4%). Multi-morbidity of chronic medical conditions was common (40% of men and 46% of women had three or more). In the overall sample, the prevalence of depression was associated with the number of chronic medical conditions (OR 1.27; CI: 1.16-1.39). In addition, SES-HK and SES-COM were significant independent variables. Conclusion In this elderly Hong Kong population, depression prevalence rose markedly with number of chronic medical conditions and SES-HK and SES-COM.